PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISSTED INDIVIDUALIZATION (T A I) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IX G SEMESTER I SMP NEGERI 3 SUKAWATI TAHUN PELAJARAN 2019/2020 - Ni Ketut Sugihantari (Widyadari, 2021)
The TAI type cooperative learning model is a learning model that forms small, heterogeneous groups with different thinking backgrounds to help each other with other students who need help. The purpose of this study was to improve students’ mathematics learning outcomes through the application of the Team Assisted Individualization (TAI) Cooperative learning model. This type of research is classroom action research. The research subjects were students of class IX G SMP Negeri 3 Sukawati in the first semester of the 2019/2020 school year totaling 38 students. In this study, two cycles were used and each cycle went through four stages of the activity process which included (1) planning, (2) action, (3) observation, and (4) evaluation and reflection. The data collection technique in this study is using the test and observation method. The results showed that only 12 students had completed the initial data, while in the first cycle there were 26 students and in the second cycle, 36 students were able to fulfill the KKM. This proves that the Team Assisted Individualization learning model can provide answers according to the purpose of this study, namely to improve mathematics learning outcomes for class IX G students of SMP Negeri 3 Sukawati.